Erasable Superconductivity in Topological Insulator Bi2Se3 Induced by Voltage Pulse. Issue 9 (23rd June 2021) - Le, Tian; Ye, Qikai; Chen, Chufan; Yin, Lichang; Zhang, Dongting; Wang, Xiaozhi; Lu, Xin
Abstract: 3D topological insulators attract much attention due to their topologically protected Dirac surface states. Doping into topological insulators or their proximity with normal superconductors can promote the realization of topological superconductivity and Majorana fermions with potential applications in quantum computation. Here, an emergent superconductivity is observed in local mesoscopic point‐contacts on the topological insulator Bi2 Se3 by applying a voltage pulse through the contacts, evidenced by the Andreev reflection peak in the point‐contact spectra and a visible resistance drop in the four‐probe electrical resistance measurements. More intriguingly, the superconductivity can be erased with thermal cycles by warming up to high temperatures (300 K) and induced again by the voltage pulse at the base temperature (1.9 K), suggesting a significance for designing new types of quantum devices. Nematic behavior is also observed in the superconducting state, similar to the case of Cu x Bi2 Se3 as topological superconductor candidates. Abstract : An emergent superconductivity is observed in local mesoscopic point‐contacts on the topological insulator Bi2 Se3 by applying a voltage pulse through the contacts. The superconductivity can be erased with thermal cycles by warming up to high temperatures (300 K) and induced again by the voltage pulse at the base temperature (1.9 K).